Profiling apoptotic patterns during forelimb development and regeneration in the newt, Notophthalmus viridescens - Vlaskalin, Tatjana (University of Ottawa (Canada), 2003)
Recent studies have found that many of the genes involved in the initial development of the limb in higher vertebrates are also expressed during regeneration of the limb in urodeles. These similarities have lead researchers to conclude that the regeneration process is a recapitulation of development and that patterning of the regenerate mimics pattern formation in development. In this work, we address the issue of whether regeneration and development are similar by examining patterns of apoptosis during these processes. In contrast to higher vertebrates, forelimb development in the newt, Notophthalmus viridescens, does not follow conventional pattern formation utilizing interdigital apoptosis as the method of individualization of the digits. Similarly, forelimb regeneration does not undergo interdigital apoptosis during cartilage condensation and digit formation in the adult. Apoptosis seems to play an important role during the wound healing stage of regeneration and again during cartilage to bone turnover during digit and radius/ulna regeneration. We suggest that urodeles have adapted a mechanism of forelimb regeneration that may re-activate developmental pathways similar to higher vertebrates, yet without cell death between the digits, and furthermore, undergo a unique mechanism of limb development in which apoptosis plays a minor role.
Keywords: Biology, Molecular.